2022
DOI: 10.3390/nu14122473
|View full text |Cite
|
Sign up to set email alerts
|

Activation of LXRs Reduces Oxysterol Lipotoxicity in RPE Cells by Promoting Mitochondrial Function

Abstract: Effective treatments for age-related macular degeneration (AMD), the most prevalent neurodegenerative form of blindness in older adults, are lacking. Genome-wide association studies have identified lipid metabolism and inflammation as AMD-associated pathogenic changes. Liver X receptors (LXRs) play a critical role in intracellular homeostases, such as lipid metabolism, glucose homeostasis, inflammation, and mitochondrial function. However, its specific role in AMD and its underlying molecular mechanisms remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…These genes are transcriptionally regulated by LXR (liver X receptor), which is activated by oxysterol-binding [45]. The role of LXR in the 7KCh response is controversial; whereas some authors showed that its activation counteracts 7KCh signaling [47][48][49], others demonstrated that LXR mediates cytokine release and cell death induced by this oxysterol [15,50]. A possible explanation of our results is that the cell mistakenly reacts to the presence of oxysterols as an excess of cholesterol and, in response, sterol biosynthesis is repressed, and cholesterol transport is favored.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are transcriptionally regulated by LXR (liver X receptor), which is activated by oxysterol-binding [45]. The role of LXR in the 7KCh response is controversial; whereas some authors showed that its activation counteracts 7KCh signaling [47][48][49], others demonstrated that LXR mediates cytokine release and cell death induced by this oxysterol [15,50]. A possible explanation of our results is that the cell mistakenly reacts to the presence of oxysterols as an excess of cholesterol and, in response, sterol biosynthesis is repressed, and cholesterol transport is favored.…”
Section: Discussionmentioning
confidence: 99%
“…Through further investigation, we found that the activation of LXR can reduce the apoptosis of RPE cells induced by oxysterol by maintaining mitochondrial membrane stasis, which jointly activates mitochondrial autophagy via the mTOR/p62 pathway to promote mitochondrial metabolism. 206 In addition to the above regulatory proteins, other molecular signals that increase the expression of ABCA1/ ABCG1 can also promote cholesterol efflux from cells and reduce the accumulation of ox-LDL, delaying disease progression.…”
Section: Role Of Cholesterol Metabolism Regulationmentioning
confidence: 99%